2015
DOI: 10.1111/ejed.12158
|View full text |Cite
|
Sign up to set email alerts
|

Learning from the Past, Looking to the Future: issues and agendas in education

Abstract: This year, EJE has marked its 50th anniversary with a special set of four linked issues, the organisation of which was inspired in part by the four pillars of learning first set out in the 1996 Delors Report, Learning: the treasure within. In this article, the authors highlight key themes that have emerged. Several of the contributing authors suggest that deepening tensions have driven education systems further away from the holistic, humanist vision of the Delors Report. At the same time, there are innovative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
(50 reference statements)
0
2
0
1
Order By: Relevance
“…Numerous authors have put forward proposals to integrate assessment into curriculum design in general [41][42][43][44][45][46][47][48][49] and communicative competence in particular [50][51][52]. The improvement in the competences requires new assessment procedures, the development of more precise measurement techniques with more people involved in the assessment and a greater balance between what needs to be measured and what can be measured [53]. It is essential that this assessment is systematically connected with teaching [54], and becomes the driving force for educational improvement [55,56].…”
Section: C2 Wordsmentioning
confidence: 99%
“…Numerous authors have put forward proposals to integrate assessment into curriculum design in general [41][42][43][44][45][46][47][48][49] and communicative competence in particular [50][51][52]. The improvement in the competences requires new assessment procedures, the development of more precise measurement techniques with more people involved in the assessment and a greater balance between what needs to be measured and what can be measured [53]. It is essential that this assessment is systematically connected with teaching [54], and becomes the driving force for educational improvement [55,56].…”
Section: C2 Wordsmentioning
confidence: 99%
“…Previous studies showed that teachers' conception of the different parts of educational process including assessment plans could affect the success of the entire educational program (Gage, 2001;Delors, 2013;Carneiro, Looney & Vincent, 2015). Furthermore, over the past few decades, education authorities have considered the studies about the teachers' conceptions of the assessment process, especially resulting from the critique of teacher's educational process ineffectiveness, as a significant issue for teacher training (Kaiser, Südkamp & Möller, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Desde que se institucionalizara este proyecto supranacional, también las universidades españolas han ido consolidando políticas en un marco de excelencia y calidad educativa conforme a estos principios (Carneiro, Looney, & Vincent-Lancrin, 2015;Khomeriki, 2015), obedeciendo a la denominada 'cuarta vía' para el cambio educativo y social, al que hoy se adscriben los entornos de educación superior, superando así la tradicional visión sobre la misión de la universidad (Oys, 2015). En la actualidad, en este proceso de construcción de mejores instituciones de enseñanza superior (Jacob, & Hellström, 2014), pasados ya dos decenios desde el surgimiento del EEES, paradojas y derivas de su sustento ético incluidas (Egron-Polak, & Hudson, 2014;Curaj et al, 2015), la innovación educativa se ha erigido en eje indiscutible de atención, análisis e investigación, con el firme propósito de liderar su implantación institucional, en unas universidades que detentan ciertos niveles de crisis y calificadas por algunos autores como instituciones «resilientes» (Pritchard, & Karlsen, 2015).…”
unclassified